Stonehenge making sense of a Prehistoric mystery - Parker Pearson, Michael 1957-; Pollard, Joshua; Richards, Colin 1953-.; Thomas, Julian 1959-.; Welham, Kate.; Dunn, Peter; Stanford, Adam; De Luis, Irene (York Council for British Archaeology, 2015)
Stonehenge is an iconic monument for people all around the world. Built around 5000 years ago, it stands for mystery and forgotten secrets waiting to be decoded. In this latest book in the Council for British Archaeology"s Archaeology for All series, Professor Mike Parker Pearson presents an up-to-date interpretation of Stonehenge and its landscape. Drawing on his years of research and excavation, the author presents a highly readable account that is lavishly illustrated with images by the renowned photographer Adam Stanford and the reconstruction artist Peter Dunn.
Includes bibliographical references (pages 157-172)
ASP-1623g donated by Lorenz Lasco
Keywords: Stonehenge (England).